PENERAPAN MODEL PEEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS VI SD NEGERI 016 KOPAH KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Syamsir Syamsir (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study is based on the result of learning of Civics students of class VI of SD Negeri 016 Kopah which is stillvery low. This study aims to improve the learning outcomes of Civics in explaining the organization of centralgovernment and Explaining the duties and authorities of the president, vice president and ministers. From thedata analysis, there is an increase of both teacher activity, student activity, and student learning result, that isteacher activity at meeting 1 cycle I the percentage is 60% (enough) and at meeting 2 increase 15% to 75%(good). In the second cycle of meeting 3 it increases 10% from 85% (very good) to 95% (very good). Judgingfrom the student activity also increased from the 1st cycle meeting I was 57.14% (enough) and at the 2ndmeeting increased by 7.14% to 64.28% (enough). In the second cycle of meeting 3 increased by 15% from 75%(good) to 90% (very good). The average base score of 61.5 increased to 70.7 in cycle I of magnitude 9.2 pointsincrease then in cycle II increased to 85.6 on the second cycle II increased 14.9 points. From the data analysisthere is an increase both from teacher activity, student activity, and student learning outcomes. It can beconcluded that the enforcement of learning model based on the problem can improve the learning outcomes ofCivics students class VI of SD Negeri 016 Kopah.